PENERAPAN METODE STORYTELLING DALAM MENINGKATKAN KEMAMPUAN MENYIMAK CERITA RAKYAT PADA SISWA KELAS VII SMP MUHAMMADIYAH 9 SUGIO - Muhammad Bayu Ferdianto; Laila Tri Lestari; Iib Marzuqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the application of the methodstorytellingin improving the listening skills of seventh-grade students of Muhammadiyah 9 Sugio Middle School. The study used a qualitative approach with a descriptive research type. Primary data sources were obtained from Indonesian language teachers and seventh-grade students through observation and interviews, while secondary data sources included teaching modules, school documents, student assignments, and documentation of learning activities. The results of the study showed that the application of the methodstorytellingThe teaching and learning process is carried out through five stages: preparation, storytelling, interaction, evaluation, and follow-up. In the preparation stage, teachers develop teaching modules, select folktales that suit the students' characteristics, and prepare strategies for storytelling. The storytelling stage is carried out expressively by utilizing intonation, expression, and body language to attract students' attention. The interaction stage encourages students to actively ask questions, discuss, and express their opinions regarding the story's content. Furthermore, the evaluation stage is carried out through questions and answers, worksheets, and assignments to retell the story. The follow-up stage involves providing feedback and reinforcing the material. Based on the results of observations, interviews, and documentation, the teaching and learning methodstorytellingIt can improve students' listening skills, demonstrated by their increased understanding of story content, their ability to identify intrinsic elements, summarize messages, and retell folktales coherently. Furthermore, this method also improves students' concentration, engagement, and motivation during the learning process.